68Ga-FAPI-04 PET-CT for molecular assessment of fibroblast activation and risk evaluation in systemic sclerosis-associated interstitial lung disease: a single-centre, pilot study - Bergmann, Christina; Distler, Jörg; Treutlein, Christoph; Tascilar, Koray; Müller, Astrid; Atzinger, Armin; Matei, Alexandru-Emil; Knitza, Johannes; Györfi, Andrea-Hermina; Lück, Anja; Dees, Clara; Soare, Alina; et al. (The Lancet Rheumatology, 2021)
Background: Interstitial lung disease (ILD) is the most common cause of death in systemic sclerosis. To date, the progression of systemic sclerosis-associated ILD is judged by the accrual of lung damage on CT and pulmonary function tests. However, diagnostic tools to assess disease activity are not available. Here, we tested the hypothesis that quantification of fibroblast activation by PET-CT using a 68Ga-labelled selective inhibitor of prolyl endopeptidase FAP (68Ga-FAPI-04) would correlate with ILD activity and disease progression in patients with systemic sclerosis-associated ILD. Methods: Between Sept 10, 2018, and April 8, 2020, 21 patients with systemic sclerosis-associated ILD confirmed by high-resolution CT (HRCT) within 12 months of inclusion and with onset of systemic sclerosis-associated ILD within 5 years or signs of progressive ILD and 21 controls without ILD were consecutively enrolled. All participants underwent 68Ga-FAPI-04 PET-CT imaging and standard-of-care procedures, including HRCT and pulmonary function tests at baseline. Patients with systemic sclerosis-associated ILD were followed for 6 months with HRCT and pulmonary function tests. We compared baseline 68Ga-FAPI-04 PET-CT uptake with standard diagnostic tools and predictors of ILD progression. The association of 68Ga-FAPI-04 uptake with changes in forced vital capacity was analysed using mixed-effects models. Follow-up 68Ga-FAPI-04 PET-CT scans were obtained in a subset of patients treated with nintedanib (follow-up between 6–10 months) to assess change over time. Findings: 68Ga-FAPI-04 accumulated in fibrotic areas of the lungs in patients with systemic sclerosis-associated ILD compared with controls, with a median standardised uptake value (SUV) mean over the whole lung of 0·80 (IQR 0·60–2·10) in the systemic sclerosis-ILD group and 0·50 (0·40–0·50) in the control group (p<0·0001) and a mean whole lung maximal SUV of 4·40 (range 3·05–5·20) in the systemic sclerosis-ILD group compared with 0·70 (0·65–0·70) in the control group (p<0·0001). Whole-lung FAPI metabolic active volume (wlFAPI-MAV) and whole-lung total lesion FAPI (wlTL-FAPI) were not measurable in control participants, because no 68Ga-FAPI-04 uptake above background level was observed. In the systemic sclerosis-ILD group the median wlFAPI-MAV was 254·00 cm3 (IQR 163·40–442·30), and the median wlTL-FAPI was 183·60 cm3 (98·04–960·70). 68Ga-FAPI-04 uptake was higher in patients with extensive disease, with previous ILD progression, or high EUSTAR activity scores than in those with with limited disease, previously stable ILD, or low EUSTAR activity scores. Increased 68Ga-FAPI-04 uptake at baseline was associated with progression of ILD independently of extent of involvement on HRCT scan and the forced vital capacity at baseline. In consecutive 68Ga-FAPI-04 PET-CTs, changes in 68Ga-FAPI-04 uptake was concordant with the observed response to the fibroblast-targeting antifibrotic drug nintedanib. Interpretation: Our study presents the first in-human evidence that fibroblast activation correlates with fibrotic activity and disease progression in the lungs of patients with systemic sclerosis-associated ILD and that 68Ga-FAPI-04 PET-CT might improve risk assessment of systemic sclerosis-associated ILD. Funding: German Research Foundation, Erlangen Anschubs-und Nachwuchsfinanzierung, Interdisziplinäres Zentrum für Klinische Forschung Erlangen, Bundesministerium für Bildung und Forschung, Deutsche Stiftung Systemische Sklerose, Wilhelm-Sander-Foundation, Else-Kröner-Fresenius-Foundation, European Research Council, Ernst-Jung-Foundation, and Clinician Scientist Program Erlangen.
CRIS-Team Scopus Importer:2021-02-26

68GA-FAPI-04 PET/CT STUDY EXTENSION FOR THE ASSESSMENT OF FIBROBLAST ACTIVATION AND RISK EVALUATION IN SYSTEMIC SCLEROSIS-RELATED INTERSTITIAL LUNG DISEASE - Bergmann, Christina; Distler, Jörg; Treutlein, Christoph; Tascilar, Koray; Müller, Astrid; Atzinger, Armin; Matei, Alexandru-Emil; Knitza, Johannes; Gyorfi, A. H.; Lueck, A.; Dees, Clara; Soare, A.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

68Ga-PSMA-11 PET/CT-derived metabolic parameters for determination of whole-body tumor burden and treatment response in prostate cancer - Schmidkonz, Christian; Cordes, Michael; Schmidt, Daniela; Bäuerle, Tobias; Goetz, Theresa Ida; Beck, Michael; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2018)
PURPOSE: We aimed at evaluating the role of 68Ga-PSMA-11 PET/CT-derived metabolic parameters for assessment of whole-body tumor burden and its capability to determine therapeutic response in patients with prostate cancer. METHODS: A total of 142 patients with biochemical recurrence of prostate cancer underwent PET/CT with [68Ga]Ga-PSMA-HBED-CC (68Ga-PSMA-11). Quantitative assessment of all 641 68Ga-PSMA-11-positive lesions in the field of view was performed to calculate PSMA-derived parameters, including whole-body PSMA tumor volume (PSMA-TV) and whole-body total lesion PSMA (TL-PSMA), as well as the established SUVmax and SUVmean values. All PET-derived parameters were tested for correlation with serum PSA levels and for association with Gleason scores. In 23 patients who underwent 68Ga-PSMA-11 PET/CT before and after therapy with either external beam radiation, androgen deprivation, or docetaxel chemotherapy, SUVmax and TL-PSMA were compared to radiographic response assessment of CT images based on RECIST 1.1 criteria and to biochemical response determined by changes of serum PSA levels. RESULTS: PSMA-TV and TL-PSMA demonstrated a significant correlation with serum PSA levels (P < 0.0001) and TL-PSMA was significantly different for different Gleason scores. The agreement rate between TL-PSMA derived from PET and biochemical response was 87% (95% confidence interval, 0.66-0.97; Cohen's κ = 0.78; P < 0.01) and, thus, higher than for SUVmax, which was 74% (95% CI, 0.52-0.90; κ = 0.55; P < 0.01). Furthermore, agreement with PSA was higher for TL-PSMA and SUVmax than for CT-based response evaluation. Discordant findings between PET and CT were most likely due to limitations of CT and RECIST in rating small lymph nodes as metastases, as well as bone involvement, which was sometimes not detectable in CT. CONCLUSION: 68Ga-PSMA-11 PET/CT-derived metabolic tumor parameters showed promising results for evaluation of treatment response. Especially, TL-PSMA demonstrated higher agreement rates with biochemical response compared to SUVmax. Larger, ideally prospective trials are needed to help to reveal the full potential of metabolic parameters derived from PET imaging with 68Ga-PSMA-11.
EVALuna2:34269

68Ga-PSMA-11 PET/CT derived quantitative volumetric tumor parameters for classification and evaluation of therapeutic response of bone metastases in prostate cancer patients - Schmidkonz, Christian; Cordes, Michael; Goetz, Theresa Ida; Prante, Olaf; Kuwert, Torsten; Ritt, Philipp; Uder, Michael; Wullich, Bernd; Goebell, Peter; Bäuerle, Tobias (Annals of Nuclear Medicine, 2019)
Background: To evaluate the role of 68Gallium prostate-specific membrane antigen-positron emission tomography/computed tomography (68Ga-PSMA-11 PET/CT) derived quantitative volumetric tumor parameters in comparison with fully diagnostic conventional CT and serum-PSA levels for classification and evaluation of therapeutic response of bone metastases in patients with metastasized prostate cancer (PC). Methods: A total of 177 men with biochemical recurrence of prostate cancer suffering from bone metastases underwent PET/CT with [68Ga] Ga-PSMA-HBED-CC (68Ga-PSMA-11). To calculate 68Ga-PSMA-11 PET quantitative volumetric tumor parameters including whole-body total-lesion PSMA (TL-PSMA), whole-body PSMA-tumor volume (PSMA-TV), as well as the established maximum standard uptake values (SUVmax) and mean standard uptake values (SUVmean), all 443 68Ga-PSMA-11-positive bone lesions in the field of view were assessed quantitatively. Quantitative volumetric tumor parameters were correlated with CT-derived volume and bone density measurements of metastatic bone lesions, serum prostate-specific antigen (PSA) levels, and Gleason Scores. In the 20 patients suffering from bone metastases who underwent 68Ga-PSMA-11 PET/CT before and after therapy, CT-derived volume and bone density measurements of metastatic lesions were compared to biochemical response determined by serum-PSA levels. Results: In 177 patients, a total of 443 68Ga-PSMA-11 PET-positive bone lesions were detected. Of these, 50 lesions (11%) were only detectable on PET but not on conventional CT. PET-positive/CT-negative bone metastases demonstrated a significantly lower PSMA uptake compared to PET-positive/CT-positive bone lesions (p < 0.05). SUVmax, SUVmean, PSMA-TV, and TL-PSMA of bone metastases were significantly higher (p < 0.05) in patients with Gleason Scores > 7 compared to those with Gleason Scores ≤ 7. In the linear regression analysis, an association was determined between SUVmean, Gleason Scores, lesion classification, and serum-PSA levels but not for CT-derived bone density measurements. No significant correlation could be found between changes of bone density and CT-derived volume measurements of metastatic bone lesions and changes of serum-PSA levels (p > 0.05) before and after therapy, while a highly significant correlation was observed for changes of PSMA-TV, TL-PSMA, and serum-PSA levels (p < 0.001). Conclusion: Our results suggest that 68Ga-PSMA-11 PET/CT might be a valuable tool for the detection and follow-up of bone metastases in patients with metastasized prostate cancer. 68Ga-PSMA-11 PET-derived quantitative volumetric parameters demonstrated a highly significant correlation with changes of serum-PSA levels during the course of therapy. No such correlation could be determined for bone density measurements of metastatic bone lesions. Compared to the fully diagnostic CT scan, a significantly higher proportion of bone metastases was detected on 68Ga-PSMA-11 PET.
CRIS-Team Scopus Importer:2019-08-02
Keywords: 68Ga-PSMA-11 PET/CT; Bone metastases; Quantitative tumor parameters; Treatment response

99mTc-MIP-1404 SPECT/CT for Assessment of Whole-Body Tumor Burden and Treatment Response in Patients With Biochemical Recurrence of Prostate Cancer - Schmidkonz, Christian; Götz, Theresa Ida; Atzinger, Armin; Ritt, Philipp; Prante, Olaf; Kuwert, Torsten; Bäuerle, Tobias; Goebell, Peter; Cordes, Michael (Clinical Nuclear Medicine, 2020)
OBJECTIVE: This study aims to investigate the value of Tc-MIP-1404 SPECT/CT for assessment of whole-body tumor burden and treatment response in patients with biochemical recurrence of prostate cancer who undergo androgen deprivation therapy (ADT) or external beam radiation therapy (EBRT). METHODS: A total of 125 patients with biochemical recurrence of prostate cancer underwent Tc-MIP-1404 SPECT/CT. All 364 prostate-specific membrane antigen (PSMA)-positive lesions in the field of view were assessed quantitatively to calculate PSMA-derived metabolic tumor parameters, including whole-body PSMA tumor volume and whole-body total lesion PSMA. These metrics were correlated with serum prostate-specific antigen (PSA) levels and Gleason scores. In a subset of 50 patients who underwent Tc-MIP-1404 SPECT/CT before the initiation of ADT or EBRT, TL-PSMA and SUVmax were compared with radiographic response assessment by CT based on RECIST 1.1 and to biochemical response (BR) determined by changes in serum PSA levels. RESULTS: Serum PSA levels correlated with SUVmax, whole-body PSMA tumor volume, and whole-body total lesion PSMA in patients with 1 and in those with more than 1 PSMA-positive lesion (P < 0.05). The correlations were significant for both well-differentiated (Gleason score ≤7) and poorly differentiated tumors (Gleason score ≥8) (P < 0.05). The agreement between TL-PSMA derived from SPECT and BR in patients who underwent Tc-MIP-1404 SPECT/CT before and after initiation of ADT was 80% (95% confidence interval [CI], 0.43-0.91; Cohen κ = 0.68; P < 0.05); in these patients, the agreement between TL-PSMA and CT was 60% (95% CI, 0.20-0.72; Cohen κ = 0.46; P < 0.05) and the agreement between BR and CT was 52% (0.07-0.61; Cohen κ = 0.34; P < 0.05). Comparable results were found for patients who underwent SPECT/CT before and after initiation of EBRT, with the strongest agreement between TL-PSMA and BR (80%; 95% CI, 0.38-0.93; Cohen κ = 0.66; P < 0.05) compared with the agreement between TL-PSMA and CT (60%; 95% CI, 0.13-0.69; Cohen κ = 0.69; P < 0.05) and between BR and CT (48%; 95% CI, 0-0.54; Cohen κ = 0.26; P = 0.11). Discordant findings between SPECT and CT were most likely due to limitations in the assessment of small lymph node metastases and bone involvement, which were detectable on SPECT but not on CT. CONCLUSIONS: The results of our study show that Tc-MIP-1404 SPECT/CT is a promising method for the evaluation of treatment response in patients with biochemical recurrence of prostate cancer who undergo either ADT or EBRT. TL-PSMA for assessment of treatment response has the strongest correlation with serum PSA levels, superior to SUVmax-based evaluation and response assessment based on CT data and RECIST 1.1.
CRIS-Team Scopus Importer:2020-06-30

99mTc-MIP-1404 SPECT/CT for Patients With Metastatic Prostate Cancer: Interobserver and Intraobserver Variability in Treatment-Related Longitudinal Tracer Uptake Assessments of Prostate-Specific Membrane Antigen-Positive Lesions - Schmidkonz, Christian; Atzinger, Armin; Götz, Theresa; Beck, Michael; Ritt, Philipp; Prante, Olaf; Kuwert, Torsten; Bäuerle, Tobias; Cordes, Michael (Clinical Nuclear Medicine, 2020)
BACKGROUND: Tc-MIP-1404 is a SPECT-suitable prostate-specific membrane antigen (PSMA) ligand for detection of prostate cancer. In patients with metastatic prostate cancer, there are no data as yet on interobserver and intraobserver variability when assessing PSMA-positive lesions for longitudinal changes of tracer uptake. METHODS: Tc-MIP-1404 SPECT/CT scans of 22 patients with metastatic prostate cancer were analyzed, and each subject was imaged at 2 separate points in time, before and after treatment. Mean interval between scans was 10 months. Three independent observers visually assessed a total of 96 PSMA-positive metastases (bone, 69; lymph node, 22; viscera, 3) or local recurrences (n = 2) for longitudinal changes in tracer uptake on planar scintigraphy and SPECT/CT. All lesions were categorized as regressive, stable, or progressive based on visual findings and on peak SUV (SUVpeak) of quantitative SPECT/CT (progressive, >30% SUVpeak increase; regressive, <30% SUVpeak decrease; or stable, all others). RESULTS: Quantitative analysis of PSMA-positive lesions yielded significantly higher interobserver agreement (90.6%; 95% confidence interval [CI], 0.83%-0.96%) than visual assessments by either SPECT/CT (76.0%; 95% CI, 0.66%-0.84%) or planar scintigraphy (56.3%; 95% CI, 0.46%-0.66%). Intermethod comparison of aggregated results yielded significantly higher agreement between quantitative and visual SPECT/CT (85.1%; 95% CI, 0.80%-0.89%), as opposed to quantitative SPECT/CT and planar scintigraphy (53.1%; 95% CI, 0.47%-0.59%) or visual SPECT/CT and planar scintigraphy (54.9%; 95% CI, 0.49%-0.61%). In visual and quantitative analysis of 96 PSMA-positive lesions, the number of discrepancies ranged from 9 (9.4%) for quantitative SPECT/CT to 42 (43.8%) for planar scintigraphy. Overall reader confidence was higher for SPECT/CT than for planar scintigraphy (P < 0.001). Intraobserver agreement was near-perfect for all methods, whether SPECT/CT (visual, all κ = 0.94-0.97; quantitative κ = 0.94-0.98) or planar scintigraphy (all κ = 0.90-0.94). CONCLUSIONS: Quantitative evaluation of longitudinal change in tracer uptake by PSMA-positive lesions measured via SPECT/CT is superior to visual interpretation of images by planar scintigraphy or SPECT/CT. Compared with visual evaluation, quantitative SPECT/CT is highly reproducible, showing near-perfect agreement among observers and higher reader confidence.
CRIS-Team Scopus Importer:2020-01-14

99m Tc-MIP-1404-SPECT/CT for the detection of PSMA-positive lesions in 225 patients with biochemical recurrence of prostate cancer - Schmidkonz, Christian; Hollweg, Claudia; Beck, Michael; Reinfelder, Julia; Götz, Theresa; Sanders, James Chester; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; et al. (Prostate, 2018)
99m Tc-MIP-1404 (Progenics Pharmaceuticals, Inc., New York, NY) is a novel, SPECT-compatible 99m Tc-labeled PSMA inhibitor for the detection of prostate cancer. We present results of its clinical use in a cohort of 225 men with histologically confirmed prostate cancer referred for workup of biochemical relapse.From April 2013 to April 2017, 99m Tc-MIP1404-scintigraphy was performed in 225 patients for workup of PSA biochemical relapse of prostate cancer. Whole-body planar and SPECT/CT images of the lower abdomen and thorax were obtained 3-4 h p.i. of 710 ± 64 MBq 99m Tc-MIP-1404. Images were visually analyzed for presence and location of abnormal uptake. In addition, quantitative analysis of the SPECT/CT data was carried out on a subset of 125 patients. Follow-up reports of subsequent therapeutic interventions were available for 59% (139) of all patients.Tracer-positive lesions were detected in 77% (174/225) of all patients. Detections occurred at the area of local recurrence in the prostate in 25% of patients (or a total of 56), with metastases in lymph nodes in 47% (105), bone in 27% (60), lung in 5% (12), and other locations in 2% (4) of patients. Detection rates were 90% at PSA levels >=2 ng/mL and 54% below that threshold. Lesional SUVmax values were, on average, 32.2 ± 29.6 (0.8-142.2), and tumor-to-normal ratios 146.6 ± 160.5 (1.9-1482.4). The PSA level correlated significantly with total uptake of MIP-1404 in tumors (P < 0.001). Furthermore, total tumor uptake was significantly higher in patients with Gleason scores >=8 compared to those with Gleason scores <=7 (P < 0.05). In patients with androgen deprivation therapy, the detection rate was significantly higher compared to patients without androgen deprivation therapy (86% vs 71%, P < 0.001). Based on 99m Tc-MIP-1404-imaging and other information, an interdisciplinary tumor board review recommended changes to treatment plans in 74% (104/139) of those patients for whom the necessary documentation was available.SPECT/CT with 99m Tc-labeled MIP-1404 has a high probability in detecting PSMA-positive lesions in patients with elevated PSA. Statistical analysis disclosed significant relationship between quantitative 99m Tc-MIP-1404 uptake, PSA level, and Gleason score.
EVALuna2:13874

Absolute quantification in SPECT - Ritt, Philipp; Vija, Hans; Hornegger, Joachim; Kuwert, Torsten (European Journal of Nuclear Medicine and Molecular Imaging, 2011)
Single-photon emission computed tomography (SPECT) allows the three-dimensional visualization of radioactivity within the human body and is widely used for clinical purposes. In SPECT, image quality is compromised by several factors including photon attenuation, photon scatter, the partial volume effect, and motion artefacts. These variables also confound the capacity of SPECT to quantify the concentration of radioactivity within given volumes of interest in absolute units, e.g. as kilobecquerels per cubic centimetre. In the last decade, considerable technical progress has been achieved in SPECT image reconstruction, involving, in particular, the development of iterative image reconstruction techniques. Furthermore, hybrid cameras integrating a SPECT camera with an X-ray CT scanner have become commercially available. These systems allow the acquisition of SPECT and CT datasets registered to each other with a high anatomical accuracy. First studies have shown that iterative SPECT image reconstruction techniques incorporating information from SPECT/CT image datasets greatly increase the accuracy of SPECT in quantifying radioactivity concentrations in phantoms and also in humans. This new potential of SPECT may improve not only diagnostic accuracy, but also dosimetry for internal radiotherapy. © 2011 Springer-Verlag.

Absolute SPECT/CT quantification of cerebral uptake of 99mTc-HMPAO for patients with neurocognitive disorders - Welz, Friedrich; Sanders, James Chester; Kuwert, Torsten; Maler, Juan; Kornhuber, Johannes; Ritt, Philipp (Nuklearmedizin-Nuclear Medicine, 2016)
It was reported from planar imaging studies that the cerebral uptake of injected 99mTc-HMPAO activity is about 4-7% in humans. Recent work has shown that modern SPECT/CT devices are able to quantify the tissue concentration of radioactivity in vivo in absolute units (Bq/ml), while avoiding the limitations of planar techniques. The aims of this study were (a) to determine the cerebral uptake of 99mTc-HMPAO in absolute units in SPECT/CT, (b) to investigate potential differences in absolute tracer uptake for patients suspected of dementia.We performed 99mTc-HMPAO SPECT/CT in 65 patients with suspected dementia. 99mTc-HMPAO uptake was determined using a previously published quantitative SPECT/CT protocol. The absolute HMPAO uptake and the results of a regionalized analysis were compared for MMSE and NINCDS-ADRDA based patient groups.The mean absolute uptake of 99mTc-HMPAO for our patient population was 4.3 ± 0.8% of the injected dose. The uptake, as well as the regionalized analysis yielded significantly different results for low (<=23) and high (>23) MMSE groups and also for some of the NINCDS-ADRDA groups.Our results show that the absolute cerebral uptake of 99mTc-HMPAO is in the range of previously reported results, obtained by planar techniques. Absolute uptake is significantly different between the patient groups.
EVALuna2:13833

A comparison of methods for adapting 177Lu dose-voxel-kernels to tissue inhomogeneities - Götz, Theresa; Schmidkonz, Christian; Lang, E. W.; Maier, Andreas; Kuwert, Torsten; Ritt, Philipp (Physics in Medicine and Biology, 2019)
In 177Lu radionuclide therapies, dosimetry is used for determining patient-individual dose burden. Standard approaches provide whole organ doses only. For assessing dose heterogeneity inside organs, voxel-wise dosimetry based on 3D SPECT/CT imaging could be applied. Often, this is achieved by convolving voxel-wise time-activity-curves with appropriate dose-voxel-kernels (DVK). The DVKs are meant to model dose deposition, and can be more accurate if modelled for the specific tissue type under consideration. In literature, DVKs are often not adapted to these inhomogeneities, or simple approximation schemes are applied. For 26 patients, which had previously undergone a 177Lu-PSMA or -DOTATOC therapy, decay maps, mass-density maps as well as tissue-type maps were derived from SPECT/CT acquisitions. These were used for a voxel-based dosimetry based on convolution with DVKs (each of size (4.8mm)3) obtained by four different DVK methods proposed in literature. The simplest only considers a spatially constant soft-tissue DVK (herein named 'constant'), while others either take into account only the local density of the center voxel of the DVK (herein named 'center-voxel') or scale each voxel linearly according to the proper mass density deduced from the CT image (herein named 'density') or considered both the local mass density as well as the direct path between the center voxel and any voxel in its surrounding (herein named 'percentage'). Deviations between resulting dose values and those from full Monte-Carlo simulations (MC simulations) were compared for selected organs and tissue-types. For each DVK method, inter-patient variability was considerable showing both under- and over-estimation of energy dose compared to the MC result for all tissue densities higher than soft tissue. In kidneys and spleen, 'constant' and 'density'-scaled DVKs achieved estimated doses with smallest deviations to the full MC gold standard (∼5%-8% underestimation). For low and high density tissue types such as lung and adipose or bone tissue, alternative DVK methods like 'center-voxel'- and 'percentage'- scaled achieved superior results, respectively. Concerning computational load, dose estimation with the DVK method 'constant' needs about 1.1 s per patient, center-voxel scaling amounts to 1.2 s, density scaling needs 1.4 s while percentage scaling consumes 860.3 s per patient. In this study encompassing a large patient cohort and four different DVK estimation methods, no single DVK-adaption method was consistently better than any other in case of soft tissue kernels. Hence in such cases the simplest DVK method, labeled 'constant', suffices. In case of tumors, often located in tissues of low (lung) or high (bone) density, more sophisticated DVK methods excel. The high inter-patient variability indicates that for evaluating new algorithms, a sufficiently large patient cohort needs to be involved.
CRIS-Team Scopus Importer:2020-02-21
Keywords: dose-voxel-kernel; dosimetry; SPECT/CT

Anatomical accuracy of abdominal lesion localization: Retrospective automatic rigid image registration between FDG-PET and MRI - Kiefer, Alexander; Kuwert, Torsten; Hahn, Dieter; Hornegger, Joachim; Uder, Michael; Ritt, Philipp (Nuklearmedizin-Nuclear Medicine, 2011)
Software-based image registration can improve the diagnostic value of imaging procedures and is an alternative to hybrid scanners. The aim of this study was to evaluate the anatomical accuracy of automatic rigid image registration of independently acquired datasets of positron emission tomography with F-deoxyglucose and abdominal magnetic resonance imaging. Patients, methods: Analyses were performed on 28 abdominal lesions from 20 patients. The PET data were obtained using a stand-alone PET camera in 14 cases and a hybrid PET/CT scanner in 9 cases. The abdominal T1- and T2-weighted MRI scans were acquired on 1.5 T MRI scanners. The mean time interval between MRI and PET was 7.3 days (0-28 days). Automatic rigid registration was carried out using a self-developed registration tool integrated into commercial available software (InSpace for Siemens Syngo). Distances between the centres of gravity of 28 manually delineated neoplastic lesions represented in PET and MRI were measured in X-, Y-, and Z-direction. The intra- (intraclass correlation 0.94) and inter- (intraclass correlation 0.86) Positronenemissionsobserver repeatability were high. Results: The average distance in all MRI sequences was 5.2 ± 7.6 mm in X-direction, 4. ± 3.7 mm in Y-direction and 6.1 ± 5.1 mm in Z-direction. There was a significantly higher misalignment in Z-direction (p < 0.05). The misalignment was not significantly different for the registration of T1- and T2- weighted sequences (p = 0.7). Conclusion: The misalignment between FDG-PET and abdominal MRI registered using an automated rigid registration tool was comparable to data reported for software-based fusion between PET and CT. Although this imprecision may not affect diagnostic accuracy, it is not sufficient to allow for pixel-wise integration of MRI and PET information. © Schattauer 2011.

Assessment of Treatment Response by 99mTc-MIP-1404 SPECT/CT: A Pilot Study in Patients With Metastatic Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (Clinical Nuclear Medicine, 2018)
BACKGROUND: We investigated the role of Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) SPECT/CT of PSMA expression in the assessment of treatment response in patients with metastatic prostate cancer. METHODS: We retrospectively analyzed Tc-MIP-1404 SPECT/CT scans from 28 patients with metastatic prostate cancer examined before initiation and after completion of therapy. Eight of these patients had been treated with androgen deprivation therapy, 10 with docetaxel, and another 10 with external beam radiotherapy. On the CT images from SPECT/CT, treatment response was assessed according to RECIST 1.1 criteria; independently from that analysis, maximal standardized uptake values (SUVmax) were quantified in representative tumor lesions and treatment response assumed at differences in SUVmax greater than 30%. Radiographic response assessment was correlated to biochemical response (BR) based on prostate-specific antigen serum levels. RESULTS: The concordance rate between SPECT and BR was 75% (95% confidence interval [CI], 0.55-0.89) (Cohen κ = 0.57; 95% CI, 0.29-0.85; P ≤ 0.01), higher than for that between SPECT and CT with 57% (95% CI, 0.37-0.76) (κ = 0.40; 95% CI, 0.14-0.65; P ≤ 0.01), as well as that between CT and BR with 50% (95% CI, 0.31-0.69) (κ = 0.31; 95% CI, 0.06-0.57, P ≤ 0.05). Discordant findings between SPECT and CT were most likely due to limitations of CT in assessing metastases in lymph nodes, as well as bone involvement, which was sometimes not detectable on CT scans. CONCLUSIONS: The high agreement between treatment response, as assessed by Tc-MIP-1404 SPECT/CT and BR, suggests a possible role of that imaging tool for monitoring treatment in metastatic prostate cancer. Larger, ideally prospective trials are needed to help to reveal the full potential of SPECT imaging of PSMA expression in that regard.
EVALuna2:34693

Assessment of treatment responses in children and adolescents with Ewing sarcoma with metabolic tumor parameters derived from 18F-FDG-PET/CT and circulating tumor DNA - Schmidkonz, Christian; Krumbholz, Manuela; Atzinger, Armin; Cordes, Michael; Goetz, Theresa Ida; Prante, Olaf; Ritt, Philipp; Schaefer, Christiane; Agaimy, Abbas; Hartmann, Wolfgang; Rössig, Claudia; Fröhlich, Birgit; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2019)
Purpose: The purpose of this study was to perform a prospective integrated analysis of 18F-fluorodeoxyglucose (18F-FDG)-positron emission tomography (PET)/computed tomography (CT) and circulating tumor DNA (ctDNA) to assess responses to multimodal chemotherapy in children and adolescents suffering from Ewing sarcoma (EwS). Methods: A total of 20 patients with histologically confirmed EwS underwent multiple 18F-FDG-PET/CT, performed at the time of each patient’s initial diagnosis and after the second and fifth induction chemotherapy block (EWING2008 treatment protocol, NCT00987636). Additional PET examinations were performed as clinically indicated in some patients, e.g., in patients suspected of having progressive or relapsing disease. All 263 18F-FDG-positive lesions in the field of view suggestive of tumor tissue were assessed quantitatively to calculate PET-derived parameters, including whole-body metabolic tumor volume (wb-MTV) and whole-body total lesion glycolysis (wb-TLG), as well as the following data: standardized uptake value (SUV)max and SUVmean. Tumor-specific ctDNA in patient plasma samples was quantified using digital droplet PCR (ddPCR), and the correlations between ctDNA levels and PET-derived parameters were analyzed. Metabolic responses to multimodal chemotherapy as assessed with PET-parameters were compared to biochemical responses as assessed with changes in ctDNA levels. Results: Twenty patients underwent a total of 87 18F-FDG-PET/CT scans, which detected 263 FDG-positive tumor lesions. Significant correlations between SUVmax, SUVmean, wb-MTV and wb-TLG values, and ctDNA levels were observed (all p < 0.0001). All patients suffering from EwS, with histology serving as gold standard, also presented with a positive corresponding ctDNA sample and a positive 18F-FDG-PET/CT examination before initiation of therapy. There were no false-negative results. Evaluation of treatment response after the fifth block of induction chemotherapy showed that the agreement between the metabolic response and biochemical response was 90%, which was statistically significant (Cohen κ = 0.62; p < 0.05). Non-detectable ctDNA after the second block of induction chemotherapy was associated with complete biochemical and metabolic responses after the fifth block of induction chemotherapy in 16/17 patients (94%). During a median follow-up period of 36 months (range: 8–104 months), four patients had tumor relapses, which, in all cases, were accompanied by an increase in plasma ctDNA levels and a positive 18F-FDG-PET/CT. No false-negative results were observed in the study cohort. Complete biochemical and metabolic responses after the fifth block of induction chemotherapy had a high positive predictive value for disease remission during the follow-up period; specifically, the positive predictive value was 88%. Conclusion: The combination of 18F-FDG-PET/CT and ctDNA quantification is a very promising noninvasive tool for assessing treatment responses and detecting tumor relapses in children and young adolescents suffering from EwS who are undergoing multimodal chemotherapy.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Circulating tumor DNA; Ewing sarcoma; Pediatric oncology; Treatment response

Auto-Gain Approach for Use with Time-of-Flight Examination in Minimally Invasive Surgery - Ritt, Philipp; Höller, Kurt Emmerich; Penne, Jochen; Schneider, Adam; Hornegger, Joachim; Feußner, Hubertus (3rd Russian-Bavarian Conference on Biomedical Engineering, 2007)

Computer-aided evaluation of the anatomical accuracy of hybrid SPECT/spiral-CT imaging of lesions localized in the neck and upper abdomen - Hahn, Dieter; Bennewitz, Christian; Kuwert, Torsten; Han, Jingfeng; Ritt, Philipp; Hahn, Dieter; Thimister, Willie; Hornegger, Joachim; Uder, Michael; Schmidt, Daniela (Nuclear Medicine Communications, 2012)
OBJECTIVE: The purpose of this study was to investigate the anatomical accuracy of hardware-based single-photon emission computed tomography/computed tomography (SPECT/CT) registration in the upper abdomen and neck. METHODS: The database consisted of 90 patients referred for SPECT/CT for diagnostic workup of either thyroid/parathyroid disease (n=46) or abdominal neuroendocrine tumours (n=44). In the first group, Tc-MIBI was used as the tracer and in the second I-metaiodobenzylguanidine (n=13), In-octreotide (n=28) or Tc-octreotide (n=3). For predefined structures represented by both modalities, the distances between the centres of gravity of their CT and SPECT representation were determined in a semiautomated manner. In cervical data sets, this analysis was performed for the submandibular salivary glands (n=92) and in abdominal data sets for 69 neoplastic foci. RESULTS: The mean distances were 5.7±2.0 mm (range: 1.84-9.67 mm) in the neck and 6.8±3.3 mm (range: 1.4-19.7 mm) in the abdomen. In 42 out of 92 of the cervical and 40 out of 69 of the abdominal data sets at least one of the X-direction-determined, Y-direction-determined, and Z-direction-determined distances was greater than the SPECT pixel width of 4.6 mm. CONCLUSION: The anatomical accuracy of hardware-based SPECT/CT fusion depends also on the region of the body studied. For example, in the neck and upper abdomen the accuracy is lower than in the lower lumbar spine. In clinical routine, SPECT/CT data sets acquired for the neck and upper abdomen should be regularly checked and corrected for SPECT/CT misalignment. This is, in particular, important when CT-based corrections of SPECT involving pixelwise data integration such as for attenuation correction are made. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.

Correction to: Assessment of treatment responses in children and adolescents with Ewing sarcoma with metabolic tumor parameters derived from 18F-FDG-PET/CT and circulating tumor DNA (European Journal of Nuclear Medicine and Molecular Imaging, (2019), 10.1007/s00259-019-04649-1) - Schmidkonz, Christian; Krumbholz, Manuela; Atzinger, Armin; Cordes, Michael; Götz, Theresa; Prante, Olaf; Ritt, Philipp; Schaefer, Christiane; Agaimy, Abbas; Hartmann, Wolfgang; Roessig, Claudia; Froehlich, Birgit; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2020)
The original version on this paper contained an error. The author names, though correctly appeared in the PDF version, were incorrectly displayed in indexing sites. This error occurred because of the incorrect tagging of their names in themetadata of this article. The purpose of this Erratum is the correction of metadata. Therefore, indexing sites should now reflect their names as Schmidkonz C, Krumbholz M, Atzinger A, Cordes M, Goetz TI, Prante O, Ritt P, Schaefer C, Agaimy A, Hartmann W, Rössig C, Fröhlich B, Bäuerle T, Dirksen U, Kuwert T, Metzler M. The original article has been corrected.
CRIS-Team Scopus Importer:2020-02-25

Data-Driven Respiratory SPECT-Gating for Pre-Radio-Embolization Determination of Liver-Lung-Shunt Fraction - Ritt, Philipp; Seidl, Kathrin; Cachovan, Michal; Vija, Alexander; Kuwert, Torsten (JOURNAL OF NUCLEAR MEDICINE, 2020)
CRIS-Team WoS Importer:2020-10-16

Deep Image Denoising in SPECT - Reymann, Maximilian; Würfl, Tobias; Ritt, Philipp; Cachovan, Michal; Stimpel, Bernhard; Maier, Andreas (European Journal of Nuclear Medicine and Molecular Imaging (2019) 46 (Suppl 1): S1–S952, 10.1007/s00259-019-04486-2, 2019)
Aim/Introduction: Single Photon Emitted Computed Tomography (SPECT) images are characterized by a high degree of image noise, which is due to the low photon count at the detector. Recently, several deep learning-based approaches for image denoising have been proposed for low-dose Computed Tomography (CT). We investigate their suitability for SPECT denoising. Materials and Methods: In order to have a groundtruth for training the networks, a Monte Carlo Simulation was set up with the SIMIND software, where in total 24 SPECT acquisitions of brains, lungs, livers and skeleton were simulated with the XCAT phantom. Pairs of noisy and clean SPECT images were then used for training the neural networks. The networks tested were the U-Net as proposed by Heinrich et al. [1], the convolutional denoising autoencoder (CNN DAE) proposed by Gondara et al. [2] and a custom U-Net that had a depth of 4 layers with 2 convolutions, Batch Normalization and ReLU in each layer. Training of the networks was done with the hyperparameters as described in the original publications. Results: The best denoising performance of the neural networks was achieved by either the CNN DAE when measured with the Structural Similarity (SSIM) index of 0.933 or by the custom U-Net with a Peak Signal to Noise Ratio (PSNR) of 30.03 dB. This corresponded to a signal quality improvement of 0.09 compared to the noisy input when measured with the SSIM, or 5.9 dB when measured with the PSNR. The denoised SPECT images showed improved visual appearance, however, gain in image quality was not as distinct as on low-dose CT data. We assume this was due to the image characteristics of SPECT images, which are characterized by few distinct image values and a more heterogeneous pixel intensity distribution compared to CT data. Conclusion: Image characteristics in SPECT pose a special challenge to deep learning-based image denoising methods, as the signal is sparse and contains a high degree of noise. We believe this, in conjunction with the limited number of samples explains the weaker benefit in performance in SPECT when compared to low-dose CT data. We assume that with a more diverse training set and specialized loss function suitable for SPECT data , we can further increase performanc
Keywords: Deep Learning; SPECT; Denoising; Monte Carlo Simulation; XCAT; Phantom

Determination of Partial-Volume Effect in Patient-Individual Kidney Phantoms for Tc-99m SPECT/CT - Grings, Andreas; Kuwert, Torsten; Ritt, Philipp (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07

Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Agarwal, Rahul; Götz, Theresa Ida; Soare, Alina; Cordes, Michael; Prante, Olaf; Prante, Olaf; Bergmann, Christina; Kleyer, Arnd; Ritt, Philipp; et al. (Annals of the Rheumatic Diseases, 2020)
Objectives To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG 4 -related disease. Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG 4 -related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68 Ga-FAP inhibitor (FAPI)-04), 18 F-fluorodeoxyglucose (FDG), MRI and histopathological assessment. In a longitudinal approach, 18 F-FDG and 68 Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Results Using combination of 68 Ga-FAPI-04 and 18 F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG 4 -related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18 F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG 4 + cells in histology, while 68 Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Conclusion FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG 4 -related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG 4 -related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team Scopus Importer:2020-10-30
Keywords: fibroblasts; health care; inflammation; outcome assessment

Disentangling inflammatory from fibrotic disease activity by fibroblast activation protein imaging - Schmidkonz, Christian; Rauber, Simon; Atzinger, Armin; Götz, Theresa Ida; Soare, A.; Cordes, Michael; Prante, Olaf; Ritt, Philipp; Bäuerle, Tobias; Köhner, Markus; Haberkorn, U.; Kuwert, Torsten; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2021)
Ziel/Aim To date, there is no valuable tool to assess fibrotic disease activity in humans in vivo in a non-invasive way. This study aims to uncouple inflammatory from fibrotic disease activity in fibroinflammatory diseases such as IgG4-related disease. Methodik/Methods In this cross-sectional clinical study, 27 patients with inflammatory, fibrotic and overlapping manifestations of IgG4-related disease underwent positron emission tomography (PET) scanning with tracers specific for fibroblast activation protein (FAP; 68Ga-FAP inhibitor (FAPI)-04), 18F-fluorodeoxyglucose (FDG), magnetic resonance imaging (MRI) and histopathological assessment. In a longitudinal approach, 18F-FDG and 68Ga-FAPI-04 PET/CT data were evaluated before and after immunosuppressive treatment and correlated to clinical and MRI data. Ergebnisse/Results Using combination of 68Ga-FAPI-04 and 18F-FDG-PET, we demonstrate that non-invasive functional tracking of IgG4-related disease evolution from inflammatory towards a fibrotic outcome becomes feasible. 18F-FDG-PET positive lesions showed dense lymphoplasmacytic infiltration of IgG4 + cells in histology, while 68Ga-FAPI-04 PET positive lesions showed abundant activated fibroblasts expressing FAP according to results from RNA-sequencing of activated fibroblasts. The responsiveness of fibrotic lesions to anti-inflammatory treatment was far less pronounced than that of inflammatory lesions. Schlussfolgerungen/Conclusions FAP-specific PET/CT permits the discrimination between inflammatory and fibrotic activity in IgG4-related disease. This finding may profoundly change the management of certain forms of immune-mediated disease, such as IgG4-related disease, as subtypes dominated by fibrosis may require different approaches to control disease progression, for example, specific antifibrotic agents rather than broad spectrum anti-inflammatory treatments such as glucocorticoids.
CRIS-Team WoS Importer:2022-01-07

Dissimilar DNA Damage to Blood Lymphocytes After 177Lu-Labeled DOTATOC or Prostate-Specific Membrane Antigen Therapy - Ritt, Philipp; Jobic, Camille; Beck, Michael; Schmidkonz, Christian; Kuwert, Torsten; Uder, Michael; Brand, Michael (Journal of Nuclear Medicine, 2021)
DNA double-strand breaks in cells of radionuclide-treated patients are quantifiable by immunofluorescence microscopy, using phosphorylation of histone-variant H2AX (γ-H2AX) to mark radiation-induced foci (RIFs). Using this method, we compared excess RIFs side by side in recipients of 177Lu-DOTATOC or 177Lu-prostate specific membrane antigen-617 (PSMA) radioligands. We also examined relations between blood dose and dose rate, RIFs, and platelet counts. Methods: Venous blood samples were obtained from 48 patients subjected to 177Lu-labeled radioligand therapy (177Lu-DOTATOC, 26; 177Lu-PSMA, 22) to quantify blood lymphocyte RIFs and blood activity concentrations at various time points, including baseline (before injection) and postinjection readings (5 min, 30 min, 4 h, 24 h, 48 h, and 72 h). Absorbed doses and dose rates to blood were derived from sequentially assessed blood activity concentrations and γ-camera imaging. Platelet levels in routine blood tests were monitored for 3 d after injection to assess responses. Results: RIF counts averaged 0.25 ± 0.15 at baseline. Postinjection RIF counts were significantly higher than baseline values, peaking at 5 min (average, 3.93 ± 2.51 min) and declining thereafter. Compared with RIF counts of 177Lu-DOTATOC, those of 177Lu-PSMA were significantly higher at 5 min after injection and significantly lower at 72 h after injection. These differences could not be fully explained by blood doses and dose rates, which were significantly higher for 177Lu-PSMA than for 177Lu-DOTATOC treatment at every time point. RIF counts overall correlated with dose rates across all time points (Pearson r = 0.78; P < 0.01) and with absorbed dose until 4 h after injection only (Pearson r = 0.42; P < 0.01). Declines in platelet concentration correlated significantly with RIFs at 72 h after injection (Pearson r = -0.34; P < 0.05). Conclusion: Although values generated by the currently used blood dosimetry model correlated with RIF counts, the difference observed in 177Lu-DOTATOC and 177Lu-PSMA treatment groups was unexplained. Significantly more RIFs were found in 177Lu-DOTATOC recipients by comparison, despite lower dose rates and blood doses, exposing a potential limitation.
CRIS-Team Scopus Importer:2021-03-19
Keywords: 177Lu-labeled therapy; DOTATOC; PSMA; radiation-induced foci; γ-H2AX

DSC Brain Perfusion Using Advanced Deconvolution Models in the Diagnostic Work-Up of Dementia and Mild Cognitive Impairment: A Semiquantitative Comparison with HMPAO-SPECT-Brain Perfusion - Schmidt, Manuel; Engelhorn, Tobias; Lang, Stefan; Lücking, Hannes; Hölter, Philip; Fröhlich, Kilian; Ritt, Philipp; Maler, Juan Manuel; Kuwert, Torsten; Kornhuber, Johannes; Dörfler, Arnd (Journal of Clinical Medicine, 2020)
Background: SPECT (single-photon emission-computed tomography) is used for the detection of hypoperfusion in cognitive impairment and dementia but is not widely available and related to radiation dose exposure. We compared the performance of DSC (dynamic susceptibility contrast) perfusion using semi- and fully adaptive deconvolution models to HMPAO-SPECT (99mTc-hexamethylpropyleneamine oxime-SPECT). Material and Methods: Twenty-seven patients with dementia of different subtypes including frontotemporal dementia (FTD) and mild cognitive impairment (MCI) received a multimodal diagnostic work-up including DSC perfusion at a clinical 3T high-field scanner and HMPAO-SPECT. Nineteen healthy control individuals received DSC perfusion. For calculation of the hemodynamic parameter maps, oscillation-index standard truncated singular value decomposition (oSVD, semi-adaptive) as well as Bayesian parameter estimation (BAY, fully adaptive) were performed. Results: Patients showed decreased cortical perfusion in the left frontal lobe compared to controls (relative cerebral blood volume corrected, rBVc: 0.37 vs. 0.27,p= 0.048, adjusted for age and sex). Performance of rBVc (corrected for T1 effects) was highest compared to SPECT for detection of frontal hypoperfusion (sensitivity 83%, specificity 80% for oSVD and BAY, area under curve (AUC) = 0.833 respectively,p< 0.05) in FTD and MCI. For nonleakage-corrected rBV and for rBF (relative cerebral blood flow), sensitivity of frontal hypoperfusion was above 80% for oSVD and for BAY (rBV: sensitivity 83%, specificity 75%, AUC = 0.908 for oSVD and 0.917 for BAY,p< 0.05 respectively; rBF: sensitivity 83%, specificity 65%, AUC = 0.825,p< 0.05 for oSVD). Conclusion: Advanced deconvolution DSC can reliably detect pathological perfusion alterations in FTD and MCI. Hence, this widely accessible technique has the potential to improve the diagnosis of dementia and MCI as part of an interdisciplinary multimodal imaging work-up. Advances in knowledge: Advanced DSC perfusion has a high potential in the work-up of suspected dementia and correlates with SPECT brain perfusion results in dementia and MCI.
CRIS-Team WoS Importer:2020-07-31

Effect of Data-Driven Respiratory Gating on Lu-177 SPECT/CT Scans - Sanders, James Chester; Kuwert, Torsten; Vija, A. Hans; Maier, Andreas; Ritt, Philipp (29th Annual EANM Congress of the European Association of Nuclear Medicine 2016, 2016)
UnivIS-Import:2017-12-18:Pub.2016.tech.IMMD.IMMD5.effect_2

Effect of Reconstruction Settings on PET-Derived Dose-Volume-Histograms after SIRT of the Liver - Roschlein, Marc; Gotz, Theresa; Schmidkonz, Christian; Beck, Michael; Kuwert, Torsten; Ritt, Philipp (JOURNAL OF NUCLEAR MEDICINE, 2020)
CRIS-Team WoS Importer:2020-10-16

Effect of reduced photon count levels and choice of normal data on semi-automated image assessment in cardiac SPECT - Wetzl, Matthias; Sanders, James Chester; Kuwert, Torsten; Ritt, Philipp (Journal of Nuclear Cardiology, 2018)
BACKGROUND: The SMARTZOOM multifocal collimator from Siemens Healthcare was developed to improve the γ-photon sensitivity in myocardial perfusion imaging without truncating the field of view. As part of the IQ-SPECT package, it may be used to reduce radiopharmaceutical dose to patients, as well as acquisition time. The aim of this study was twofold: (1) to evaluate the influence of dose reduction in semi-automated MPI scoring, with focus on different strategies for the choice of normal data (count-matched, full-count), and (2) to evaluate the effect of dose reduction afforded by Siemens' IQ-SPECT package. METHODS: 50 patients underwent Tc-99m-sestamibi one-day stress/rest SPECT/CT. Multiple levels of count reduction were generated using binomial thinning. Using Corridor 4DM, summed stress score (SSS) was calculated using either count-matched or full-count normal data. Studies were classified as low-risk (SSS < 4) or intermediate/high-risk (SSS ≥ 4). RESULTS: Count reduction using count-matched normal data increases false-normal rate and decreases sensitivity. With full-count normal data, count reduction increases false-hypoperfusion rate, leading to decreased specificity. Altogether, rate of reclassification was significant at roughly 67% dose and below. CONCLUSION: Significant bias results from count level of normal data relative to actual patient data. Compared to standard LEHR, IQ-SPECT should allow for significant dose reduction.
EVALuna2:212295

Estimation of [177Lu]PSMA-617 tumor uptake based on voxel-wise 3D Monte Carlo tumor dosimetry in patients with metastasized castration resistant prostate cancer - Götz, Theresa Ida; Lang, Elmar Wolfgang; Prante, Olaf; Cordes, Michael; Kuwert, Torsten; Ritt, Philipp; Ludwig, Bernd; Schmidkonz, Christian (Nuklearmedizin-Nuclear Medicine, 2020)
Objective Patients with advanced prostate cancer are suitable candidates for [ 177Lu]PSMA-617 therapy. Integrated SPECT/CT systems have the potential to improve the accuracy of patient-specific tumor dosimetry. We present a novel patient-specific Monte Carlo based voxel-wise dosimetry approach to determine organ and total tumor doses (TTD). Methods 13 patients with histologically confirmed metastasized castration-resistant prostate cancer were treated with a total of 18 cycles of [ 177Lu]PSMA-617 therapy. In each patient, dosimetry was performed after the first cycle of [ 177Lu]PSMA-617 therapy. Regions of interest were defined manually on the SPECT/CT images for the kidneys, spleen and all 295 PSMA-positive tumor lesions in the field of view. The absorbed dose to normal organs and to all tumor lesions were calculated by a three dimensional dosimetry method based on Monte Carlo Simulations. Results The average dose values yielded the following results: 2.59 ± 0.63 Gy (1.67-3.92 Gy) for the kidneys, 0.79 ± 0.46 Gy (0.31-1.90 Gy) for the spleen and 11.00 ± 11.97 Gy (1.28-49.10 Gy) for all tracer-positive tumor lesions. A trend towards higher TTD was observed in patients with Gleason Scores > 8 compared to Gleason Scores ≤ 8 and in lymph node metastases compared to bone metastases. A significant correlation was determined between the serum-PSA level before RLT and the TTD (r = -0.57, p < 0.05), as well as between the TTD with the percentage change of serum-PSA levels before and after therapy was observed (r = -0.57, p < 0.05). Patients with higher total tumor volumes of PSMA-positive lesions demonstrated significantly lower kidney average dose values (r = -0.58, p < 0.05). Conclusion The presented novel Monte Carlo based voxel-wise dosimetry calculates a patient specific whole-body dose distribution, thus taking into account individual anatomies and tissue compositions showing promising results for the estimation of radiation doses of normal organs and PSMA-positive tumor lesions.
CRIS-Team Scopus Importer:2020-07-31
Keywords: dosimetry; prostate cancer; PSMA; radioligand therapy

Evaluation of a Highly-Automated Dosimetry Tool-Chain for Lu-177-Therapies - Ritt, Philipp; Cachovan, M.; Vija, A. H.; Kuwert, Torsten (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2019)
CRIS-Team WoS Importer:2021-10-18

Factors affecting accuracy of S values and determination of time-integrated activity in clinical Lu-177 dosimetry - Götz, Th I.; Schmidkonz, Christian; Lang, E. W.; Maier, Andreas; Kuwert, Torsten; Ritt, Philipp (Annals of Nuclear Medicine, 2019)
Introduction: In any radiotherapy, the absorbed dose needs to be estimated based on two factors, the time-integrated activity of the administered radiopharmaceutical and the patient-specific dose kernel. In this study, we consider the uncertainty with which such absorbed dose estimation can be achieved in a clinical environment. Methods: To calculate the total error of dose estimation we considered the following aspects: The error resulting from computing the time-integrated activity, the difference between the S-value and the patient specific full Monte Carlo simulation, the error from segmenting the volume-of-interest (kidney) and the intrinsic error of the activimeter. Results: The total relative error in dose estimation can amount to 25.0% and is composed of the error of the time-integrated activity 17.1%, the error of the S-value 16.7%, the segmentation error 5.4% and the activimeter accuracy 5.0%. Conclusion: Errors from estimating the time-integrated activity and approximations applied to dose kernel computations contribute about equally and represent the dominant contributions far exceeding the contributions from VOI segmentation and activimeter accuracy.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Lu-177 dosimetry; Monte Carlo simulations; S-values; SPECT/CT; Time integrated activity

Feature Loss After Denoising of SPECT Projection Data using a U-Net - Reymann, Maximilian; Massanes, Francesc; Ritt, Philipp; Cachovan, Michal; Kuwert, Torsten; Vija, A. Hans; Maier, Andreas (Feature Loss After Denoising of SPECT Projection Data using a U-Net, 2020)
It has been long known that denoising of SPECT projection data from multi channel collimators harbors the danger that features are filtered away as distinction between noise and signal in the 2D projection image does not consider the tomographic information (see Vija, Yahil et al.). We investigate if an approach using Neural Networks can overcome the past issues, by training a U-Net on Monte Carlo Simulations of the XCAT phantom. Although error metrics indicate improvement of signal statistics, we observe a loss of image features after the reconstruction. We show that when using OSEM reconstruction without denoising in projection domain, these features can be preserved.<br
Keywords: SPECT; Denoising; Monte Carlo Simulation; XCAT Phantom; SIMIND; U-Net

First Experience With SPECT/CT Using a 99mTc-Labeled Inhibitor for Prostate-Specific Membrane Antigen in Patients With Biochemical Recurrence of Prostate Cancer - Reinfelder, Julia; Kuwert, Torsten; Beck, Michael; Sanders, James C.; Ritt, Philipp; Schmidkonz, Christian; Hennig, Peter; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter (Clinical Nuclear Medicine, 2017)
Prostate-specific membrane antigen (PSMA) is overexpressed in most prostate cancers (PCs). Here, we report our first experience using the Tc-labeled PSMA inhibitor MIP-1404 (Progenics Pharmaceuticals, Inc, Tarrytown, NY) in 60 patients with biochemically recurrent PC.Whole-body planar scintigraphy and SPECT/CT of the lower abdominal pelvic region of 60 patients with biochemical relapse of PC were analyzed retrospectively. In these subjects, an average dose of 733.1 ± 49.5 MBq (19.8 ± 1.3 mCi) Tc-labeled MIP-1404 was injected 4 to 5 hours prior to imaging. In addition to visual evaluation, SUVmax were determined in the tumor lesions using a previously developed protocol for quantitative SPECT/CT.In 42 of 60 patients, Tc-MIP-1404-positive lesions could be detected (70%; 95% confidence interval [CI], 0.58-0.82). Twenty patients had Tc-MIP-1404-positive lymph nodes suggestive of metastasis, 14 patients had pathological uptake in the prostate region indicative of local recurrence, and for another 19 patients, there was tracer accumulation in the skeleton (n = 18) or lungs (n = 1). Detection rate was 91.4% (95% CI, 0.82-1) at prostate-specific antigen levels greater than 2 ng/mL and 40.0% (95% CI, 0.21-0.59) at lower prostate-specific antigen values (P < 0.01). Of the 60 patients, in total, 82 positive lesions were analyzed quantitatively. Average SUVmax of the lesions was 16.3 ± 21.6 with a range of 1.7 to 142.9.Tc-labeled PSMA inhibitor MIP-1404 is a promising SPECT tracer for detection of locally recurrent or metastatic prostate cancer.
EVALuna2:13859

Fully Automated Data-Driven Respiratory Signal Extraction From SPECT Images Using Laplacian Eigenmaps - Sanders, James Chester; Ritt, Philipp; Kuwert, Torsten; Vija, A. Hans; Maier, Andreas (IEEE Transactions on Medical Imaging, 2016)
We propose a data-driven method for extracting a respiratory surrogate signal from SPECT list-mode data. The approach is based on dimensionality reduction with Laplacian Eigenmaps. By setting a scale parameter adaptively and adding a series of post-processing steps to correct polarity and normalization between projections, we enable fully-automatic operation and deliver a respiratory surrogate signal for the entire SPECT acquisition. We validated the method using 67 patient scans from three acquisition types (myocardial perfusion, liver shunt diagnostic, lung inhalation/perfusion) and an Anzai pressure belt as a gold standard. The proposed method achieved a mean correlation against the Anzai of 0.81 ± 0.17 (median 0.89). In a subsequent analysis, we characterize the performance of the method with respect to count rates and describe a predictor for identifying scans with insufficient statistics. To the best of our knowledge, this is the first large validation of a data-driven respiratory signal extraction method published thus far for SPECT, and our results compare well with those reported in the literature for such techniques applied to other modalities such as MR and PET.
EVALuna2:13863

Ga-68-FAPI-04 PET/CT for molecular assessment of fibroblast activation and risk evaluation in systemic sclerosis-related interstitial lung disease - Schmidkonz, Christian; Distler, Jörg; Treutlein, Christoph; Atzinger, Armin; Prante, Olaf; Ritt, Philipp; Goetz, T.; Bäuerle, Tobias; Cordes, Michael; Köhner, Markus; Kuwert, Torsten; Ramming, Andreas; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2021)
CRIS-Team WoS Importer:2022-01-07

GATE Monte Carlo simulations for variations of an integrated PET/MR hybrid imaging system based on the Biograph mMR model - Aklan, Bassim; Jakoby, B. W.; Watson, C. C.; Braun, Harald; Ritt, Philipp; Quick, H. H. (Physics in Medicine and Biology, 2015)
A simulation toolkit, GATE (Geant4 Application for Tomographic Emission), was used to develop an accurate Monte Carlo (MC) simulation of a fully integrated 3T PET/MR hybrid imaging system (Siemens Biograph mMR). The PET/MR components of the Biograph mMR were simulated in order to allow a detailed study of variations of the system design on the PET performance, which are not easy to access and measure on a real PET/MR system. The 3T static magnetic field of the MR system was taken into account in all Monte Carlo simulations. The validation of the MC model was carried out against actual measurements performed on the PET/MR system by following the NEMA (National Electrical Manufacturers Association) NU 2-2007 standard. The comparison of simulated and experimental performance measurements included spatial resolution, sensitivity, scatter fraction, and count rate capability. The validated system model was then used for two different applications. The first application focused on investigating the effect of an extension of the PET field-of-view on the PET performance of the PET/MR system. The second application deals with simulating a modified system timing resolution and coincidence time window of the PET detector electronics in order to simulate time-of-flight (TOF) PET detection. A dedicated phantom was modeled to investigate the impact of TOF on overall PET image quality. Simulation results showed that the overall divergence between simulated and measured data was found to be less than 10%. Varying the detector geometry showed that the system sensitivity and noise equivalent count rate of the PET/MR system increased progressively with an increasing number of axial detector block rings, as to be expected. TOF-based PET reconstructions of the modeled phantom showed an improvement in signal-to-noise ratio and image contrast to the conventional non-TOF PET reconstructions. In conclusion, the validated MC simulation model of an integrated PET/MR system with an overall accuracy error of less than 10% can now be used for further MC simulation applications such as development of hardware components as well as for testing of new PET/MR software algorithms, such as assessment of point-spread function-based reconstruction algorithms.
EVALuna2:13836

Hybrid Imaging (PET-Computed Tomography/PET-MR Imaging) of Bone Metastases - Schmidkonz, Christian; Ellmann, Stephan; Ritt, Philipp; Roemer, Frank; Guermazi, Ali; Uder, Michael; Kuwert, Torsten; Bäuerle, Tobias (PET Clinics, 2019)
Bone metastases are a common source of osseous malignancy in the skeleton and affect up to 70% of all cancer patients. Hybrid imaging modalities including positron emission tomography (PET)/computed tomography (CT) and PET/MRI play an increasing role for the detection and follow-up of metastatic disease, especially in monitoring treatment response upon local or systemic therapy. This review summarizes current applications of PET/CT and PET/MRI in the clinical setting for imaging of metastases.
CRIS-Team WoS Importer:2020-02-21

Ictal SPECT in patients with rapid eye movement sleep behaviour disorder - Mayer, Geert; Bitterlich, Marion; Kuwert, Torsten; Ritt, Philipp; Stefan, Hermann (Brain, 2015)
Rapid eye movement sleep behaviour disorder is a rapid eye movement parasomnia clinically characterized by acting out dreams due to disinhibition of muscle tone in rapid eye movement sleep. Up to 80-90% of the patients with rapid eye movement sleep behaviour disorder develop neurodegenerative disorders within 10-15 years after symptom onset. The disorder is reported in 45-60% of all narcoleptic patients. Whether rapid eye movement sleep behaviour disorder is also a predictor for neurodegeneration in narcolepsy is not known. Although the pathophysiology causing the disinhibition of muscle tone in rapid eye movement sleep behaviour disorder has been studied extensively in animals, little is known about the mechanisms in humans. Most of the human data are from imaging or post-mortem studies. Recent studies show altered functional connectivity between substantia nigra and striatum in patients with rapid eye movement sleep behaviour disorder. We were interested to study which regions are activated in rapid eye movement sleep behaviour disorder during actual episodes by performing ictal single photon emission tomography. We studied one patient with idiopathic rapid eye movement sleep behaviour disorder, one with Parkinson's disease and rapid eye movement sleep behaviour disorder, and two patients with narcolepsy and rapid eye movement sleep behaviour disorder. All patients underwent extended video polysomnography. The tracer was injected after at least 10 s of consecutive rapid eye movement sleep and 10 s of disinhibited muscle tone accompanied by movements registered by an experienced sleep technician. Ictal single photon emission tomography displayed the same activation in the bilateral premotor areas, the interhemispheric cleft, the periaqueductal area, the dorsal and ventral pons and the anterior lobe of the cerebellum in all patients. Our study shows that in patients with Parkinson's disease and rapid eye movement sleep behaviour disorder-in contrast to wakefulness-the neural activity generating movement during episodes of rapid eye movement sleep behaviour disorder bypasses the basal ganglia, a mechanism that is shared by patients with idiopathic rapid eye movement sleep behaviour disorder and narcolepsy patients with rapid eye movement sleep behaviour disorder.
EVALuna2:13851

Impact of Point-Spread Function Modeling on PET Image Quality in Integrated PET/MR Hybrid Imaging - Aklan, Bassim; Oehmigen, Mark; Beiderwellen, Karsten; Ruhlmann, Marcus; Paulus, Daniel; Jakoby, Bjoern W.; Ritt, Philipp; Quick, Harald H. (Journal of Nuclear Medicine, 2016)
The aim of this study was to systematically assess the quantitative and qualitative impact of including point-spread function (PSF) modeling into the process of iterative PET image reconstruction in integrated PET/MR imaging.All measurements were performed on an integrated whole-body PET/MR system. Three substudies were performed: an (18)F-filled Jaszczak phantom was measured, and the impact of including PSF modeling in ordinary Poisson ordered-subset expectation maximization reconstruction on quantitative accuracy and image noise was evaluated for a range of radial phantom positions, iteration numbers, and postreconstruction smoothing settings; 5 representative datasets from a patient population (total n = 20, all oncologic (18)F-FDG PET/MR) were selected, and the impact of PSF on lesion activity concentration and image noise for various iteration numbers and postsmoothing settings was evaluated; and for all 20 patients, the influence of PSF modeling was investigated on visual image quality and number of detected lesions, both assessed by clinical experts. Additionally, the influence on objective metrics such as changes in SUVmean, SUVpeak, SUVmax, and lesion volume was assessed using the manufacturer-recommended reconstruction settings.In the phantom study, PSF modeling significantly improved activity recovery and reduced the image noise at all radial positions. This effect was measurable only at a high number of iterations (>10 iterations, 21 subsets). In the patient study, again, PSF increased the detected activity in the patient's lesions at concurrently reduced image noise. Contrary to the phantom results, the effect was notable already at a lower number of iterations (>1 iteration, 21 subsets). Lastly, for all 20 patients, when PSF and no-PSF reconstructions were compared, an identical number of congruent lesions was found. The overall image quality of the PSF reconstructions was rated better when compared with no-PSF data. The SUVs of the detected lesions with PSF were substantially increased in the range of 6%-75%, 5%-131%, and 5%-148% for SUVmean, SUVpeak, and SUVmax, respectively. A regression analysis showed that the relative increase in SUVmean/peak/max decreases with increasing lesion size, whereas it increases with the distance from the center of the PET field of view.In whole-body PET/MR hybrid imaging, PSF-based PET reconstructions can improve activity recovery and image noise, especially at lateral positions of the PET field of view. This has been demonstrated quantitatively in phantom experiments as well as in patient imaging, for which additionally an improvement of image quality could be observed.
EVALuna2:13858

Influence of CT metal artifact reduction on SPECT/CT quantification of bone scintigraphy - Retrospective study for selected types of metal implants - Kugler, Amelie; Kuwert, Torsten; Ritt, Philipp; Grings, Andreas (Nuklearmedizin-Nuclear Medicine, 2022)
Aim Implanted metal prostheses can cause severe artifacts in reconstructed computed tomography (CT) images. To reduce the diagnostic impact of these artifacts and improve attenuation correction in single photon emission computed tomography (SPECT), an algorithm of iterative metal artifact reduction (iMAR) for SPECT/CT systems was developed. The aims of this study were (a) to assess the difference in visual image quality by comparing CT and SPECT images reconstructed with and without iMAR and (b) to determine the influence of iMAR on quantitative (99m) Tc-uptake in SPECT/CT. Methods This retrospective study includes 21 patients with implanted metal prostheses who underwent SPECT/CT bone scintigraphy. CT data were reconstructed with iMAR and without (noMAR) and were used for attenuation correction of SPECT data for xSPECT Quant and xSPECT Bone reconstruction. The effect of iMAR on image quality was evaluated by visual analysis and the effect on quantitative SPECT/CT was assessed by measuring HU values and absolute uptake values (kBq/mL) in volumes of interest (VOIs). Results There was a significant reduction of visible metal artifacts with iMAR (p<0.01) in the CT images, but visual differences in the SPECT images were minor. The values of quantitative tracer uptake in VOIs near metal implants were lower for iMAR vs. noMAR xSPECT Quant (p<0.01). Only VOIs near metal showed significant differences in HU values, which were 14.6% lower for iMAR CT (p<0.01). Conclusion The use of iMAR reduces metal artifacts in CT and improves the perceived image quality. Although in some cases a significant difference in the quantitative evaluation of SPECT/CT was observed, the influence of iMAR can be considered small in relation to other factors in the clinical setting.
CRIS-Team WoS Importer:2022-08-19

Influence of Photon Count-Level on Semi-Automatic Image Assessment in Myocardial Perfusion Imaging - Sanders, James Chester; Wetzl, Matthias; Götz, Theresa; Kuwert, Torsten; Ritt, Philipp (2018)
EVALuna2:212304

Longitudinal analysis of bone metabolism using SPECT/CT and (99m)Tc-diphosphono-propanedicarboxylic acid: comparison of visual and quantitative analysis - Beck, Michael; Sanders, James Chester; Ritt, Philipp; Reinfelder, Julia; Kuwert, Torsten (EJNMMI Research, 2016)
The therapy response of osseous metastases (OM) is commonly monitored by bone scintigraphies (BS). The aim of this study was to compare visual evaluation of changes in tracer uptake with quantitation in absolute units in OMs; 52 OMs from 19 patients who underwent BS with SPECT/CT at time points one and two (TP1/2) were analyzed retrospectively, with an average of 10.3 months between TP1 and 2. Tracer uptake in lesions was visually compared by two independent readers in both planar scintigraphies and SPECT/CT across both TPs and classified as regressive, stable, or progressive. Quantitative analysis was performed by measuring peak standardized uptake values (SUV). Based on quantitation, lesions were similarly classified as regressive (>30 % decrease), progressive (>30 % increase), or stable (rest). If available, uptake in reference regions in the lower thoracic or lumbar spine was used for normalization.In OMs at TP1 and TP2, mean SUVpeak (±SD) was found to be 20.4 (±20.8) and 16.4 (±11.5), respectively. For the reference region, mean SUVmean was 5.6 (±1.9) and 4.9 (±2.2). Agreement between quantitative and visual assessment was only moderate, with an average Cohen's kappa of 0.42 for planar scintigraphy and 0.62 for SPECT/CT. Discrepancies occurred in between 11 and 22 of the 52 lesions, depending on the reader and whether planar or SPECT imaging was considered.Compared to measuring uptake in absolute units, visual evaluation of skeletal scintigraphies for change in tumor metabolism yields inconsistent results in roughly one third of the cases.
EVALuna2:13860

Monte-Carlo Simulation and Experimental Validation of a Gamma-Camera Prototype Featuring a Novel Collimation Technique - Meinderink, T.; Osterloh, P.; Osterloh, K.; Götz, Theresa; Kuwert, Torsten; Ritt, Philipp (2018)
EVALuna2:212303

Normal Values of Skeletal Tc-99m-labelled Bisphosphonate Uptake in SPECT/CT - Ritt, Philipp; Heim, Patrick; Grings, Andreas; Beck, Michael; Kuwert, Torsten (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07

Particle filter de-noising of voxel-specific time-activity-curves in personalized 177Lu therapy - Götz, Theresa; Götz, Th I.; Lang, E. W.; Schmidkonz, Christian; Maier, Andreas; Kuwert, Torsten; Ritt, Philipp (Zeitschrift für Medizinische Physik, 2019)
Background: Currently, there is a high interest in 177Lu targeted radionuclide therapies, which could be attributed to favorable results obtained from 177Lu compounds targeting neuro-endocrine and prostate tumors. SPECT based dosimetry could be used for deriving dose values for individual voxels, as is the standard in external-beam radiation-therapy (EBRT). For this a time-activity-curve (TAC) at voxel resolution and also a voxel-wise modeling of radiation energy deposition are necessary. But a voxel-wise determination of TACs is problematic, since several confounding factors exist, such as e.g. poor count-statistics or registration inaccuracies, which add noise to the observed activity states. A particle filter (PF) is a class of methods which applies regularization based on a model of the temporal evolution of activity states. The aim of this study is to introduce the application of PFs for de-noising of per-voxel time-activity curves. Methods: We applied a PF for de-noising the TACs of 26 patients, who underwent 177Lu-DOTATOC or -PSMA therapy. The TACs were obtained from fully-quantitative, serial SPECT(/CT) data, acquired at 4 h, 24 h, 48 h, 72 h p.i. The model used in the PF was a mono-exponential decay and its free parameters were determined based on objective criteria. The time-integrated activities (TIA) resulting from the PF (PFF) were compared to the results of a mono-exponential fit (SF) of individual voxels in several volumes of interest (kidneys, spleen, tumors). Additionally, an organ-averaged TIA was derived from whole-organ VOIs and subsequent curve-fitting. This whole-organ TIA was also compared to the whole-organ TIAs obtained from summation of the voxel-wise TIAs from PFF and SF. Results: The number of particles was set to 1000. Optimal values for noise of observations and noise of the model were 0.25 and 0.5, respectively. The deviation of whole-organ TIAs from conventional organ-based dosimetry and the summation of the voxel-wise TIAs was substantial for SF (kidneys −22.3%, spleen −49.6%, tumor −60.0%), as well as for PFF (kidneys −37.1%, spleen −57.9%, tumor −70.9%). The distribution of voxel-wise half-lives resulting from the PFF method was considerably closer to the organ-averaged value, and the number of implausibly long half-lives (>physical HL) was reduced. Conclusion: The PFF leads to voxel-wise half-lives, which are more plausible than those resulting from SF. However, one has to admit that voxel-wise fitting generally leads to considerable deviations from the organ-averaged TIA as obtained by conventional whole-organ evaluation. Unfortunately, we did not have ground-truth TIA of our patient data and proper ground-truth could even be impossible to obtain. Nevertheless, there are strong indicators that particle filtering can be used for reducing voxel-wise TAC noise.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Dosimetry; Nuclear medicine; Time-activity-curve; Voxelwise

Patient-Specific Phantoms for Tc-99m Brain Perfusion Imaging with SPECT/CT - Grings, Andreas; Reymann, M.; Vija, A. H.; Kuwert, Torsten; Ritt, Philipp (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07

Pattern Recognition in Medical and Health Engineering - Hornegger, Joachim; Höller, Kurt Emmerich; Ritt, Philipp; Borsdorf, Anja; Niedermeier, Hans-Peter (Union Aktuell, 2008)
UnivIS-Import:2015-07-08:Pub.2008.tech.IMMD.IMMD5.patter_7

PET/MRI and PET/CT: is there room for both at the top of the food chain? - Kuwert, Torsten; Ritt, Philipp (European Journal of Nuclear Medicine and Molecular Imaging, 2016)
EVALuna2:13856

Potential Limitations of Established Blood-Dosimetry Models for Lu-177 Therapy - Ritt, Philipp; Jobic, C.; Grings, Andreas; Beck, Michael; Schmidkonz, Christian; Kuwert, Torsten; Uder, Michael; Brand, Michael (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07

PSMA SPECT/CT with 99mTc-MIP-1404 in biochemical recurrence of prostate cancer: predictive factors and efficacy for the detection of PSMA-positive lesions at low and very-low PSA levels - Schmidkonz, Christian; Götz, Theresa; Kuwert, Torsten; Ritt, Philipp; Prante, Olaf; Bäuerle, Tobias; Goebell, Peter; Cordes, Michael (Annals of Nuclear Medicine, 2019)
Background: The in vivo expression of the prostate-specific membrane antigen (PSMA) can be investigated using the SPECT-suitable tracer 99mTc-MIP-1404. We investigated the performance of 99mTc-MIP-1404 PSMA SPECT/CT in the detection of PSMA-positive tumor lesions in patients suffering from biochemical recurrence of prostate cancer presenting with serum levels of the prostate-specific antigen (PSA) below 1 ng/mL. Methods: We retrospectively analyzed 99mTc-MIP-1404-SPECT/CT scans of 50 patients (25 with low PSA levels between > 0.5 and 1 ng/mL and 25 with very low PSA levels between 0.2 and 0.5 ng/mL) that had undergone whole-body planar scintigraphy and SPECT/CT of the thorax, abdomen and pelvis 3–4 h p.i. of 691 ± 72 MBq 99mTc-MIP-1404. All datasets were evaluated for the presence and location of PSMA-positive tumor lesions, in which maximal standardized uptake values (SUVmax) were also measured. Based on the results of the quantitative evaluation as well as on biochemical and histological parameters, predictive factors for a positive 99mTc-MIP-1404 scan result were determined. The influence of 99mTc-MIP-1404 PSMA SPECT/CT on further therapy planning was assessed, based on the decision-making of the interdisciplinary tumor board. Results: Pathological 99mTc-MIP-1404 uptake was detected in a total of 25 patients (50%). In the very low PSA subgroup, detection rates of PSMA-positive lesions suggestive of tumor recurrence were 44%, in the low-PSA subgroup 56%. Gleason scores ≥ 8 and the presence of antiandrogen deprivation therapy were further significant predictors of pathological 99mTc-MIP-1404 uptake. This was paralleled by significantly higher lesional SUVmax patients with PSA levels > 0.5 ng/mL and Gleason scores ≥ 8 compared to those without these two features. Changes in therapeutic strategy following MIP-1404 imaging were recommended by the interdisciplinary tumor board in 25/50 of patients. Conclusion: 99mTc-MIP-1404 PSMA-SPECT/CT demonstrated a high performance in detecting PSMA-positive lesions suggestive of tumor recurrence in patients with biochemical recurrence of prostate cancer and low and very low serum PSA levels. Results from MIP-1404 PSMA SPECT/CT have therapeutic impact in one-half of the patients examined by this technology.
CRIS-Team Scopus Importer:2019-10-29
Keywords: Low PSA levels; MIP-1404; Prostate cancer; PSMA; Quantitative SPECT/CT; SPECT/CT

Quantitative Analysis of Multimodal Skeletal SPECT/CT Reconstructions in Diagnosing Medication-related Osteonecrosis of the Jaw - Beck, Michael; Rugel, Gregor; Reinfelder, Julia; Kuwert, Torsten; Ritt, Philipp; Kreißel, Sebastian; Schlittenbauer, Tilo (Nuklearmedizin-Nuclear Medicine, 2021)
Aim Our goal was to assess visual and quantitative aspects of multimodal skeletal SPECT/CT reconstructions (recon) in differentiating necrotic and healthy bone of patients with suspected MRONJ. Methods Prior to surgery, 20 patients with suspected MRONJ underwent SPECT/CT of the jaw 3-4 hours after injection of Tc-99m-DPD (622±112.4 MBq). SPECT/CT data were reconstructed using the multimodal xSPECT Bone and xSPECT Quant algorithms as well as the OSEM-algorithm FLASH 3D. For analysis, we divided the jaw into 12 separate regions. Both xSPECT Bone and FLASH 3D datasets were scored on a four-point scale (VIS xSPECT; VIS F3D), based on the intensity of localized tracer uptake. In F3D and xSPECT Quant datasets, local tracer uptake of each region was recorded as semi-quantitative uptake ratio (SQR F3D) or SUVs, respectively. ROC analysis was performed. Postoperative histologic results served as gold standard. Results VIS F3D, VIS xSPECT and SQR F3D did not differ significantly in diagnostic accuracy (VIS xSPECT sensitivity=0.64; specificity=0.89). Of the quantitative parameters, SUVpeak yielded the best interobserver reproducibility. SUVpeak was 9.9±7.1 (95%CI: 7.84-11.95) in MRONJ regions, as opposed 3.6±1.8 (95% CI:3.36-3.88) elsewhere, with a cutpoint of 4.5 (sensitivity=0.83; specificity=0.80). Absolute quantitation significantly surpassed VIS and SQR (p<0.05) in accuracy and interobserver agreement (SUVpeak: κ=0.92; VIS xSPECT: κ=0.61; SQR F3D κ=0.66). Conclusion Absolute quantitation proved significantly more accurate than visual and semi-quantitative assessment in diagnosing MRONJ, with higher interobserver agreement.
CRIS-Team Scopus Importer:2021-08-27
Keywords: MRONJ; Multimodal SPECT reconstruction; Multimodale SPECT/CT; Quantitative SPECT/CT

Quantitative bias for SPECT imaging in kidneys due to respiratory motion - a simulation study - Sanders, James Chester; Kuwert, Torsten; Vija, A. Hans; Maier, Andreas; Ritt, Philipp (Kongressausgabe 56. Jahrestagung der Deutschen Gesellschaft für Nuklearmedizin, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.quanti_2

Quantitative Bias from Respiratory Motion and Finite System Resolution for SPECT Imaging of Kidneys A Simulation Study - Sanders, James Chester; Kuwert, Torsten; Vija, A. Hans; Maier, Andreas; Ritt, Philipp (Journal of Nuclear Medicine (Supplement 1), 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.quanti_6

Quantitative radionuclide imaging of bone metastases - De Schepper, Stijn; Ritt, Philipp; Van den Wyngaert, Tim; Kuwert, Torsten (Quarterly Journal of Nuclear Medicine and Molecular Imaging, 2019)
By improving the localization of foci of pathological tracer uptake and offering information on their computed tomography (CT) morphology, single photon emission computed tomography (SPECT)/CT hybrid imaging has considerably improved the diagnostic accuracy of skeletal scintigraphy. SPECT/CT also has the potential to measure tracer uptake in vivo in absolute units. The present article reviews the methodology for and the potential clinical impact of quantitative skeletal scintigraphy.
CRIS-Team Scopus Importer:2019-09-27

Quantitative SPECT/CT Imaging of Lu-177 with In Vivo Validation in Patients Undergoing Peptide Receptor Radionuclide Therapy - Sanders (III), James; Kuwert, Torsten; Hornegger, Joachim; Ritt, Philipp (Molecular Imaging and Biology, 2015)
UnivIS-Import:2015-04-14:Pub.2014.tech.IMMD.IMMD5.quanti
Keywords: Quantitative SPECT; [Lu-177]DOTATATE; Peptide receptor radionuclide therapy; Dosimetry

Quantitative SPECT/CT-Technique and Clinical Applications - Ritt, Philipp; Kuwert, Torsten (Recent Results in Cancer Research, 2020)
The continuous development of SPECT over the past 50 years has led to improved image quality and increased diagnostic confidence. The most influential developments include the realization of hybrid SPECT/CT devices, as well as the implementation of attenuation correction and iterative image reconstruction techniques. These developments have led to a preference for SPECT/CT devices over SPECT-only systems and to the widespread adoption of the former, strengthening the role of SPECT/CT as the workhorse of Nuclear Medicine imaging. New trends in the ongoing development of SPECT/CT are diverse. For example, whole-body SPECT/CT images, consisting of acquisitions from multiple consecutive bed positions in the manner of PET/CT, are increasingly performed. Additionally, in recent years, some interesting approaches in detector technology have found their way into commercial products. For example, some SPECT cameras dedicated to specific organs employ semiconductor detectors made of cadmium telluride or cadmium zinc telluride, which have been shown to increase the obtainable image quality by offering a higher sensitivity and energy resolution. However, the advent of quantitative SPECT/CT which, like PET, can quantify the amount of tracer in terms of Bq/mL or as a standardized uptake value could be regarded as most important development. It is a major innovation that will lead to increased diagnostic accuracy and confidence, especially in longitudinal studies and in the monitoring of treatment response. The current work comprises two main aspects. At first, physical and technical fundamentals of SPECT image formation are described and necessary prerequisites of quantitative SPECT/CT are reviewed. Additionally, the typically achievable quantitative accuracy based on reports from the literature is given. Second, an extensive list of studies reporting on clinical applications of quantitative SPECT/CT is provided and reviewed.
CRIS-Team Scopus Importer:2020-07-10

Recent Developments in SPECT/CT - Ritt, Philipp (Seminars in Nuclear Medicine, 2022)
The debut of multimodal Single Photon Emission Computed Tomography/X-ray Computed Tomography (SPECT/CT) has signified an important advancement of Nuclear Medicine imaging by allowing for high-quality attenuation correction and co-registration/fusion of metabolic and anatomical images. This progress in SPECT instrumentation continued and resulted in the clinical application of several new techniques, such as for example, semiconductive Cadmium-Zinc-Telluride (CZT) detectors, quantification of radiopharmaceutical uptake in absolute units, whole-body SPECT acquisitions with multiple bed positions, and novel non-parallel hole collimators. Many other new methods were reported from literature during the last years, but still await implementation in clinical routine. Here, examples are multipinhole collimators, iterative reconstruction with Monte-Carlo projectors, list-mode SPECT acquisitions, and quantitative imaging of alpha-emitters. For the future, it could be expected that deep-learning approaches would be applied for Nuclear Medicine imaging, confirming the promising results reported by research groups. More efforts should be made for standardizing quantitative SPECT, to allow for inter-site comparability of radiopharmaceutical uptake and derived quantities such as dosimetry results. The awaited market authorization of several SPECT-imageable therapeutic radiopharmaceuticals will drive the interest in SPECT/CT and ensure that it remains the workhorse of Nuclear Medicine.
CRIS-Team Scopus Importer:2022-03-18

SPECT/CT With the PSMA Ligand 99mTc-MIP-1404 for Whole-Body Primary Staging of Patients With Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp (Clinical Nuclear Medicine, 2018)
BACKGROUND: Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) is a novel ligand binding to prostate-specific membrane antigen suitable for SPECT. There are, as yet, no data concerning its use in whole-body primary staging and its interobserver variability in patients with prostate cancer (PC) prior to therapy. METHODS: A search of our clinical database from April 2013 to May 2017 yielded 93 patients with histologically confirmed cancer in whom Tc-MIP-1404 SPECT/CT had been performed for primary whole-body staging before therapy. Whole-body planar and SPECT/CT images of the lower abdomen and thorax had been obtained 3 to 4 hours postinjection of 706 ± 72 MBq Tc-MIP-1404. Images were visually analyzed for extent and location of abnormal uptake by 2 experienced nuclear physicians. Interobserver agreement for detection of primary tumor and metastatic lesions was assessed. In addition, SUVs of prostate-specific membrane antigen-positive regions of the prostate were determined in all patients, and from these, a variable reflecting total tumor load in the prostate gland was calculated (TUprostate). Follow-up reports of subsequent therapeutic interventions were available in 52 (56%) of all patients with a median follow-up of 18 months. RESULTS: In 90 (97%) of 93 patients, prostate uptake above background was detected as correlate of the histologically diagnosed PC. Forty-eight lymph node and 29 bone metastases were detected in 16 and 9 patients, respectively. In addition, 3 patients had disseminated bone metastases. No distant organ metastases were found. Interobserver agreement was high for the overall scan result (97%), as well as for the detection of the primary tumor (97%), of lymph node metastases (97%), and of bone metastases (99%). Recurrence of PC occurred in 5 patients in whom follow-up was available (10%). TUprostate was significantly higher in patients with Gleason scores of 8 or greater compared with patients with Gleason scores of 7 or less and at prostate-specific antigen (PSA) serum levels of 10 ng/mL or greater compared with PSA serum levels of 10 ng/mL or less. TUprostate of greater than 26 in the primary tumor predicted the occurrence of lymph node or bone metastases with a sensitivity of 82% and specificity of 76%. CONCLUSIONS: MIP-1404 SPECT/CT has a high accuracy and low interobserver variability in the diagnosis of PC and allows detection of lymph node and bone metastases in a significant proportion of as yet untreated PC patients. TUprostate is correlated with Gleason score and PSA serum concentration and allows prediction of the occurrence of lymph node and bone metastases with moderate accuracy at primary staging.
EVALuna2:32786

Technik und physikalische Aspekte der SPECT / CT - Ritt, Philipp; Hornegger, Joachim; Kuwert, Torsten (Der Nuklearmediziner, 2011)

The magnitude of the partial volume effect in SPECT imaging of the kidneys: a phantom study - Grings, Andreas; Jobic, Camille; Kuwert, Torsten; Ritt, Philipp (EJNMMI Physics, 2022)
Background: Single-photon emission computed tomography (SPECT) can cause an over- or underestimation of tissue activity concentration due to limitations in spatial resolution compared to the structures under study. This is commonly referred to as partial volume effect (PVE). Ideally, the PVE should be controlled for and corrected. One such correction method involves determining recovery coefficients (RC) from phantom measurements. In the literature, several studies applying simplified geometries are available. In this study, we aimed to determine kidney PVE for realistic kidney geometries. Furthermore, we proposed a new surrogate metric for predicting the extent of PVE in kidneys. Material and methods: Based on patients’ CT data, we manufactured fillable phantoms using a 3D-printer. Nine cortex-only and ten whole-parenchyma phantoms were obtained, and one ellipsoidal phantom for comparison. To measure PVE, we placed the phantoms in a torso phantom and filled them with a specified activity concentration. The phantoms’ RCs were determined from fully quantitative SPECT/CT acquisitions at three different target-to-background ratios (TBRs). Additionally, the surface area-to-volume (SA:V) ratio was determined for all phantoms and correlated with RCs. Results: For SPECT reconstructions with 36 iterations, average RC ± one standard deviation at a 10-to-1 TBR was 76.3 ± 1.5% and 48.4 ± 8.3% for whole-parenchyma and cortex-only phantoms, respectively. The RC for the ellipsoidal phantom was 85.4%. The RC for whole-parenchyma was significantly higher than for cortex-only phantoms (p < 0.01). The RC variance was significantly higher for cortex-only phantoms (p < 0.01). A highly significant correlation of the SA:V ratio and RC was found for all phantoms. (R2 of linear regression was between 0.96 and 0.98.) Conclusion: Changes in the specific shape of the kidneys cause large changes in PVE magnitude. Therefore, RCs derived from more simple phantoms are most likely insufficient to correct the PVE in patient images. Furthermore, one should account for the fact that intra-renal activity distribution significantly influences the extent of PVE. Additionally, we found that the SA:V ratio excellently models kidney RCs; potentially, this approach could also be applied to other geometries and represents an alternative to full imaging process simulations to determine the extent of PVE.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 3D-print; CT; Kidney; Phantom; Recovery coefficient; SPECT

Three-dimensional Monte Carlo-based voxel-wise tumor dosimetry in patients with neuroendocrine tumors who underwent 177Lu-DOTATOC therapy - Goetz, Th. I.; Lang, E. W.; Prante, Olaf; Maier, Andreas; Cordes, Michael; Kuwert, Torsten; Ritt, Philipp; Schmidkonz, Christian (Annals of Nuclear Medicine, 2020)
Background: Patients with advanced neuroendocrine tumors (NETs) of the midgut are suitable candidates for 177Lu-DOTATOC therapy. Integrated SPECT/CT systems have the potential to help improve the accuracy of patient-specific tumor dosimetry. Dose estimations to target organs are generally performed using the Medical Internal Radiation Dose scheme. We present a novel Monte Carlo-based voxel-wise dosimetry approach to determine organ- and tumor-specific total tumor doses (TTD). Methods: A cohort of 14 patients with histologically confirmed metastasized NETs of the midgut (11 men, 3 women, 62.3 ± 11.0 years of age) underwent a total of 39 cycles of 177Lu-DOTATOC therapy (mean 2.8 cycles, SD ± 1 cycle). After the first cycle of therapy, regions of interest were defined manually on the SPECT/CT images for the kidneys, the spleen, and all 198 tracer-positive tumor lesions in the field of view. Four SPECT images, taken at 4 h, 24 h, 48 h and 72 h after injection of the radiopharmaceutical, were used to determine their effective half-lives in the structures of interest. The absorbed doses were calculated by a three-dimensional dosimetry method based on Monte Carlo simulations. TTD was calculated as the sum of all products of single tumor doses with single tumor volumes divided by the sum of all tumor volumes. Results: The average dose values per cycle were 3.41 ± 1.28 Gy (1.91–6.22 Gy) for the kidneys, 4.40 ± 2.90 Gy (1.14–11.22 Gy) for the spleen, and 9.70 ± 8.96 Gy (1.47–39.49 Gy) for all 177Lu-DOTATOC-positive tumor lesions. Low- and intermediate-grade tumors (G 1–2) absorbed a higher TTD compared to high-grade tumors (G 3) (signed-rank test, p = < 0.05). The pre-therapeutic chromogranin A (CgA) value and the TTD correlated significantly (Pearson correlation: = 0.67, p = 0.01). Higher TTD resulted in a significant decrease of CgA after therapy. Conclusion: These results suggest that Monte Carlo-based voxel-wise dosimetry is a very promising tool for predicting the absorbed TTD based on histological and clinical parameters.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Dosimetry; Monte Carlo simulations; Neuroendocrine tumors

U-Net for Multi-Organ Segmentation of SPECT Projection Data - Mürschberger, Nina; Reymann, Maximilian; Cachovan, Michal; Ritt, Philipp; Vija, Hans; Maier, Andreas (U-Net for Multi-Organ Segmentation of SPECT Projection Data, 2020)
This work explores the usage of deep learning techniques for segmentation of anatomical structures on SPECT data. Previous works applied deep learning techniques on CT scans of anatomical information and afterwards registered the resulting segmentation mask on the SPECT data. We train a U-Net on 2D projection data extracted from Lu-177 MELP SPECT scans aim to predict the areas corresponding to liver, spleen and kidney. The challenging acquisition technique comes along with low resolution, low contrast between the abdominal organs and variations in size, shapes and location due to the differences in patients` anatomies. We use the dice similarity coefficient to evaluate the network. Visual validation, confusion matrix and recall shall evaluate the worthiness of further investigations in deep learning techniques used for nuclear medicine. We achieve a mean dice similarity coefficient of 72% and a validation loss of 11%, encouraging us to further investigate our approach.<br
Keywords: SPECT; Segmentation; Deep Learning; Lu-177

U-Net for SPECT Image Denoising - Reymann, Maximilian; Würfl, Tobias; Stimpel, Bernhard; Ritt, Philipp; Cachovan, Michal; Vija, A. Hans; Maier, Andreas (2019 IEEE Nuclear Science Symposium and Medical Imaging Conference Proceedings (NSS/MIC), 2019)
Single Photon Emitted Computed Tomography (SPECT) is characterized by low photon counts and high degrees of image noise. In this work we investigate deep image postprocessing methods for improving image quality in SPECT projections and propose a new architecture. Specifically, the residual U-Net proposed by Heinrich et al. for low-dose Computed Tomography (CT) and the Convolutional Denoising Autoencoder (CNN DAE) by Gondara et al. were tested for their performance for denoising SPECT projections. Reference images without noise and scatter were obtained from SPECT Monte Carlo simulations of 24 different XCAT phantoms of brains, lungs, livers and skeletons using the SIMIND software. These clean images were then used as training target for the neural networks. Additionally, we propose a U-Net architecture that is more suited for SPECT image denoising, consisting of 4 layers, each with 2 blocks of convolution, batch normalization and ReLU. Our results showed that the proposed U-Net outperforms the residual U-Net and the CNN DAE with a PSNR of 38.25 dB, compared to 27.95 dB and 28.25 dB, respectively. It was shown that the characteristics of the SPECT data posed a challenge to the neural networks, as there are only few distinct photon count values at the detector available and these are superimposed with a high degree of image noise, compared to low-dose CT. Our proposed network was able to decrease the noise within the phantom and additionally decreased the background noise in the image. The image quality was improved by 14.15 dB compared to the noisy input image, demonstrating the suitability of our network. We believe that with increased size and diversity of our dataset we can further boost the performance.<br
Keywords: SPECT; Denoising; Monte Carlo Simulation; XCAT Phantom; SIMIND; U-Net

Whole body non-rigid PET/CT alignment using synthetic CT generation from non-attenuation corrected F-18-FDG PET images with a 3D CycleGAN - Khushu, Surbhi; Von Gall, C. C. A.; Reymann, M.; Sibille, L.; Spottiswoode, B.; Ritt, Philipp; Kuwert, Torsten; Shah, V. (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07